PENGARUH STRES KERJA, LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. BANK KALBAR CABANG NGABANG - B11111152, JULIAR FANTARA B11111152 (Jurnal Manajemen Update, 2015)
This research aimed to examine and analyze the influence of work stress, work environment and compensation on the perfomance of the employees at PT. Bank Kalbar branch Ngabang, the causal survey research method was used in this study, which is a method of reseacrh that shows the cause and effect between the independent and dependent variables to measure the strenght of the influence that occurs between variables. The samples in this study were the employees of PT. Bank Kalbar branch Ngabang with a total of 64 respondents. The data collection method was using the questionnaire. The analysis technique used in this research was the multiple linier regression, and the data were processed using the software application of SPSS version 16. The result showed that partially work environment variable and compensation variable had a significant influence while work stress variable had no significant influence on the perfomance of the employees at PT. Bank Kalbar branch Ngabang. Keywords : Work Stress, Work Environment, Compensation and Perfomance.